Golf anatomy - Davies, Craig; Davies, Craig (Human Kinetics, 2010)
"See your golf game as you never have before. See what it takes to improve consistency and performance on the links. Golf Anatomy will show you how to lower your score by increasing strength, power, and range of motion for longer drives and more accurate shots.--Publisher's description.